THE INFUSION OF AFRICAN JURISPRUDENCE ON LEGAL DEFENCES INTO JUDICIAL DELIBERATIONS Bulelwa Ndamase v Development Bank of Southern Africa Limited D 8073/2020 [2022] (ZAKZDHC) (30 May 2022) - Aubrey Manthwa (Obiter, 2023)
It is often said that customary law is unwritten, as its knowledge system is not recorded in statutes and codifications. Tracing its earliest origins can prove difficult, largely because African communities have historically lived independently of one another, observing norms and practices that differ from one community to another. In previous eras, Africans lived according to values such as a sense of communal belonging, collective ownership of assets and the communal life that characterised the African tradition. All these elements developed into an African normative system that catered for justice and human rights. The fortunes of customary law, however, changed after contact with colonialism. Section 11(1) of the Black Administration Act (BAA) 38 of 1927, for example, afforded courts the discretion to apply customary law in all disputes concerning African people as disputants, provided that customary law was not against public policy and natural justice. This repugnancy proviso therefore limited the application of customary law. Section 11(1) of the BAA was repealed in 1988 by the Law of Evidence Amendment Act 45 of 1988, which was framed in similar terms to the BAA, and in terms of which courts could take judicial notice of customary law if it could be readily ascertainable. As a result, courts could merely strike down any African practice or norm that they deemed to be inconsistent with principles of public policy and natural justice. The interim Constitution contained a specific provision speaking to the cardinal African concept of ubuntu. However, this concept did not find space in the 1996 Constitution. Yet, ubuntu had already informed the basis for the abolition of the death penalty in one of South Africa’s most seminal judgments in a first case that came before a full panel of the Constitutional Court. The Constitutional Court stressed the importance of infusing African jurisprudence or indigenous knowledge systems into judicial pronouncements. This had become apparent in the wake of the ill-treatment of customary law as a subordinate legal system vis-à-vis common law. Other courts have subsequently made commitments that customary law and its value systems would be afforded space as an independent legal system away from the prowling eye of the common law. Also, in Gumede v President of the Republic of South Africa (2009 (3) SA 152 (CC) par 22), the Constitutional Court confirmed that customary law “lives side by side with the common law and legislation”. Notwithstanding these assertions, courts have not given effect or found an avenue to allow customary law to be integrated in decision-making. It must be stated that customary law differs from indigenous law as customary law emerges from the latter. Customary law is people’s adaptation of indigenous law to socio-economic changes. This gives effect to the value of indigenisation that scholars have written about and has also become a value that institutions of higher learning have embraced to form part of their curriculum design and transformation. A long journey still lies ahead for the process of indigenisation, especially in Western-style courts, but there are tools and a rich body of literature with which to work. The role of developing indigenous languages has also become important and requires attention.